A Morphological Comparison of Urban Tissues of Trani and Galata - Agirbas, Asli; Ardaman, Emel (Journal of Architecture and Urbanism, 2015)
The morphological tissues of two Mediterranean coastal colonies; Galata and Trani have been examined in macro-scale, together with the variations, linked to the distinct phases of economic and socio-cultural change in different time cycles, which is one of the bases of the Conzen approach. The effects of road-system changes, city walls, urban regulations and socio-cultural tissues on the urban morphologies of the cities throughout the history were investigated during the comparison of these two cities. Common features were found in both regions with respect to the urban morphology of newly developing and re-structured areas. According to the old map analysis, the urban growth inside the walls, the growth after the destruction of the walls, the developments of the minority regions and its effects on the urban texture, and the gridal growth of newly developing and destroyed regions are similar in Trani and Galata. Moreover, it was attempted to apply urban regulations which would largely demolish the region, in these two Mediterranean colonies with the effect of Hausmannization. In addition, during the urban regulatory initiatives in Galata, though it was not appropriate to the region, an attempt was made to apply a radial urban square, which is a western urban strategy. Galata, although it is a part of Istanbul, in contrast with the urban growth of Istanbul, shows a western type growth, very similar to that for Trani, which has been a most important buffer point of the trade in Adriatic Sea. This study demonstrates that there is an intermingling between urban form and culture, in addition to the contextualisation of ‘global’ cultural influences on local regulations and urban development practices, and has further investigated their effects at a particular time and, in that in another period such urban coexistence has been lost.